Rational Design of Hierarchically Open‐Porous Spherical Hybrid Architectures for Lithium‐Ion Batteries. Issue 6 (20th December 2018) - Yun, Sol; Bak, Seong‐Min; Kim, Sanghyeon; Yeon, Jeong Seok; Kim, Min Gyu; Yang, Xiao‐Qing; Braun, Paul V.; Park, Ho Seok
Abstract: Controlling the internal microstructure and overall morphology of building blocks used to form hybrid materials is crucial for the realization of deterministically designed architectures with desirable properties. Here, integrative spray‐frozen (SF) assembly is demonstrated for forming hierarchically structured open‐porous microspheres (hpMSs) composed of Fe3 O4 and reduced graphene oxide (rGO). The SF process drives the formation of a radially aligned microstructure within the sprayed colloidal droplets and also controls the overall microsphere morphology. The spherical Fe3 O4 /rGO hpMSs contain interconnected open pores, which, when used as a lithium‐ion battery anode, enables them to provide gravimetric and volumetric capacities of 1069.7 mAh g −1 and 686.7 mAh cm −3, much greater than those of samples with similar composition and different morphologies. The hpMSs have good rate and cycling performance, retaining 78.5% capacity from 100 to 1000 mA g −1 and 74.6% capacity over 300 cycles. Using in situ synchrotron X‐ray absorption spectroscopy, the reaction pathway and phase evolution of the hpMSs are monitored enabling observation of the very small domain size and highly disordered nature of Fe x O y . The reduced capacity fade relative to other conversion systems is due to the good electrical contact between the pulverized Fe x O y particles and rGO, the overall structural integrity of the hpMSs, and the interconnected open porosity. Abstract : Hierarchically structured porous hybrid microspheres, are synthesized via spray‐frozen assembly and investigated as anodes for lithium‐ion batteries. Ice crystal growth during freezing controls their internal open pore structure; their hybrid composition and internal bonding is shown to improve their rate and cyclic performance. Their reaction pathway and phase evolution are investigated via in situ X‐ray absorption spectroscopy.